Analysis of the Role of the Midwife in Increasing Exclusive Breast Milk at Mare Community Health Center Technical Implementation Unit - Sulfianti Sulfianti; Hasliana Haslan (Journal La Medihealtico, 2021)
The kind of research that was utilized in this study was an analytical questionnaire. In this study, a cross-sectional design was employed to collect data. Sixty-six individuals were included in the samples that fulfilled the requirements. The findings revealed that 1) the midwife's attitude toward promoting exclusive breastfeeding at the UPT Puskesmas (Community Health Center) Mare had no impact on the outcomes of the study. The results of the chi square test revealed that the p-value was 0,089, indicating that the hypothesis was correct (0,05). There is an association between midwife assistance and an increase in exclusive breastfeeding at the University of Puskesmas Mare, according to the findings of the chi square test (p-value =0,007 for exclusive breastfeeding at the UPT Puskesmas Mare) (0,05). The rise in exclusive breastfeeding at the UPT Puskesmas Mare may be attributed to the midwifery program, according to the findings. The results of the chi square test reveal that the p-value is 0,0002, which indicates a significant difference (0,05). 4) Midwife assistance had a 12,7-fold higher impact on the rise in exclusive breastfeeding, with a p-value of 0.028 0.05 for the effect of midwife support. The midwife program, on the other hand, had a moderate impact on the rise in exclusive breastfeeding, with a p-value of 0,038 0.05 and a moderate effect of 11,1 times on the increase in exclusive breastfeeding.